2014
DOI: 10.1097/mcc.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative respiratory failure

Abstract: PRF is a life-threatening event that is challenging for the surgical team. Risk prediction scales based on large population studies are being developed and validated. We need high-quality trials of preventive measures, particularly those related to ventilator use in both high risk and general populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 53 publications
1
13
0
3
Order By: Relevance
“…The use of colloids (albumin in milliliters per kilogram per hour) was a modifiable variable independently associated with PPC development. This is consistent with previous literature suggesting an effect of large fluid administration in worsening surgical outcomes, 25,27,28 and our observed lower administration of fluids (in milliliters per kilogram per hour) to patients without PPCs. Interestingly, recent studies have shown an increased PPC risk in surgical patients with hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 94%
“…The use of colloids (albumin in milliliters per kilogram per hour) was a modifiable variable independently associated with PPC development. This is consistent with previous literature suggesting an effect of large fluid administration in worsening surgical outcomes, 25,27,28 and our observed lower administration of fluids (in milliliters per kilogram per hour) to patients without PPCs. Interestingly, recent studies have shown an increased PPC risk in surgical patients with hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 94%
“…According to the literature data atelectasis in the pulmonary tissue are formed mainly during intraoperative and in the early postoperative period (14,15). Resolving atelectasis in the lungs after cardiac surgery often takes several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ARISCAT (Assess Respiratory Risk in Surgical Patients in Catalonia) uses age, preoperative O 2 saturation, surgical incision (upper abdomen or thoracic), duration of surgery, and other clinical risks (eg, anemia, recent respiratory infection, or emergency surgery). 12 There are no prospective studies on the utilization of preoperative risk scores to direct the application of enhanced monitoring.…”
Section: Risk Factors For Respiratory Compromisementioning
confidence: 99%